2011
DOI: 10.1177/0739986310388021
|View full text |Cite
|
Sign up to set email alerts
|

Latino/a Student Misbehavior and School Punishment

Abstract: Although Latino/as are the fastest growing segment of the U.S. student population, Latino/a youth face a number of educational hurdles, such as disproportionate school punishment. This topic is particularly relevant today in the midst of the current social, political, and economic debate over the influence of Latino/a immigration in the US school system. This study draws from the Educational Longitudinal Study of 2002 and utilizes hierarchical linear modeling (HLM) to analyze the relationships between gender, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 21 publications
5
86
1
Order By: Relevance
“…Disciplinary disparities for other racial/ethnic categories have been less thoroughly studied, with less consistent results. While Peguero and Shekarkhar (2011) found disparities in discipline for first-and-third generation Latino students, others have reported rates of out-of-school suspension for Latino students not significantly different from white students (Horner, Fireman, & Wang, 2010;McFadden et al, 1992;Skiba, Peterson, & Williams, 1997). In a national examination of self-reported data concerning discipline outcomes, Wallace, Goodkind, Wallace, and Bachman (2008) reported that Native American students were over-represented and Asian students underrepresented in school discipline, in general, and suspension in particular.…”
Section: Differential Effects: Who Is At Risk For Exclusionary Discipmentioning
confidence: 95%
“…Disciplinary disparities for other racial/ethnic categories have been less thoroughly studied, with less consistent results. While Peguero and Shekarkhar (2011) found disparities in discipline for first-and-third generation Latino students, others have reported rates of out-of-school suspension for Latino students not significantly different from white students (Horner, Fireman, & Wang, 2010;McFadden et al, 1992;Skiba, Peterson, & Williams, 1997). In a national examination of self-reported data concerning discipline outcomes, Wallace, Goodkind, Wallace, and Bachman (2008) reported that Native American students were over-represented and Asian students underrepresented in school discipline, in general, and suspension in particular.…”
Section: Differential Effects: Who Is At Risk For Exclusionary Discipmentioning
confidence: 95%
“…While the intent of zerotolerance policies were to create a safe school environment for all students with fair application of consequences, the policies have been found to be problematic and discriminatory, particularly against Latino students (Peguero & Shekarkhar, 2011;Verdugo, 2002;Wheeler & Richey, 2010). As with academic referrals, Latino students are significantly overrepresented in disciplinary referrals and actions when compared with other groups (Noguera, 2003a;Peguero & Shekarkhar, 2011;Skiba et al, 2011).…”
Section: Overrepresentation Of Latino Students In Disciplinary Actionsmentioning
confidence: 97%
“…Several investigators (e.g., Peguero & Shekarkhar, 2011;Skiba et al, 2011, Verdugo, 2002 have concluded that Latino students are significantly more likely to be referred for disciplinary actions for lesser offenses. For example, Peguero and Shekarkhar investigated the patterns of school disciplinary actions among Latino students and White students and found a disproportional rate of punishment based on generational status and ethnicity.…”
Section: Overrepresentation Of Latino Students In Disciplinary Actionsmentioning
confidence: 98%
“…Rothwell (2009) mentioned the above four elements are linked to delinquency of organizational misbehavior. Scholars Baek, Kang and Park (2004); Peguero & Shekarkhar (2011) also applied this theory in their studies based on university and school students. Whereas Solomons (2010) applied this theory to explain about decision making process of police officers.…”
Section: Social Learning Theory (Aker 1963)mentioning
confidence: 99%